Boundary conditions for sediment input into the river Rhine: soils, sediments and slope processes - Thiemeyer, Heinrich; Blümel, Wolf Dieter; Dambeck, Rainer; Dieckmannn, Bodo; Eberle, Joachim; Glade, Thomas; Hecht, Stefan; Houben, Peter; Moldenhauer, Klaus-Martin; Schrott, Lothar; Schulte, Achim; Vogt, Richard; et al. (ERDKUNDE, 2005)
For the River Rhine catchment, sediment yield, transport and storage can only be understood considering the catchment’s environmental settings as well as human impact for the last six millennia. The general significance of soil parent material on slopes and in loess areas is stressed in order to better understand Holocene sediment fluxes in the River Rhine catchment. An example from the northern Upper Rhine graben reveals the situation on floodplains. In particular, the loess regions are the areas of early human impact. Some regional studies from the Rhine-Main region, the Neckar catchment, the Höri peninsula at Lake Constance and the Hegau region highlight human impact with respect to local geomorphologic, pedologic and geological controls. Depending on the specific environmental setting, sediment propagation, spatial and temporal storage as well as sediment yield differ considerably. Landslides and their varying impact are addressed with respect to type, magnitude and frequency of occurrence and river system characteristics. However, in alpine environments sediment supply from landslides is assumed to have minor significance for the River Rhine catchment.